Electrically evoked ABR during cochlear implantation and postoperative development of speech and hearing abilities in infants with common cavity deformity as a type of inner ear malformation. (2nd January 2020) - Kaga, Kimitaka; Minami, Shujiro; Enomoto, Chieko
Abstract: Background: The electrically evoked auditory brainstem response (eABR) during cochlear implantation in common cavity (CC) deformity has not been clinically well studied. Aim/Objective: To investigate the eABR wave configuration during cochlear implantation, the postoperative development of hearing, and educational settings in infants with CC deformity. Materials and Methods: Nine infants who were congenitally deaf and found to have CC deformity and suspected cochlear nerve deficiency by temporal bone CT and MRI were studied. All of them underwent sequential and unilateral cochlear implantation and their eABRs were recorded during the surgery. The postoperative development was followed up. Results: eABRs of all the nine infants with CC deformity showed that the mean peak of the evoked wave V (eV) was the same as that in controls at latencies but was twofold higher than that in controls at thresholds and their postoperative hearing thresholds improved markedly. Conclusion and Significance: The brainstem auditory pathways of the infants were considered intact on the basis of the eV peak latencies in the eABRs. The postoperative development of their speech and hearing abilities and their educational settings varied, probably because of the twofold higher thresholds of their eABRs and limited number of auditory neural units.